2009
DOI: 10.2136/vzj2008.0142
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Properties of Variously Weathered Granitic Bedrock in Headwater Catchments

Abstract: Recent studies have emphasized the importance of bedrock in hydrologic processes occurring in headwater catchments. To understand water flow processes through variously weathered bedrock, we measured the saturated hydraulic conductivity, Ks, and water retention characteristics of weakly to highly weathered Tanakami granite and Rokko granite core samples. On the basis of these core‐scale properties, along with the core shape and in situ Ks measurements, we defined two groups of bedrock: CM class (weakly weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 48 publications
3
57
1
Order By: Relevance
“…Katsura et al [2009] reported that the hydraulic conductivity of weathered granite bedrock (10 -5 -10 -3 cm s -1 ) is higher than that of weakly weathered bedrock (10 -8 cm s -1 ) in deeper layers. Based on intensive observations of the SiO 2 concentrations of groundwater and streamwater, Katsuyama et al [2005] showed that groundwater flow within a permeable weathered granite bedrock contributed to streams year-round in one small headwater catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Katsura et al [2009] reported that the hydraulic conductivity of weathered granite bedrock (10 -5 -10 -3 cm s -1 ) is higher than that of weakly weathered bedrock (10 -8 cm s -1 ) in deeper layers. Based on intensive observations of the SiO 2 concentrations of groundwater and streamwater, Katsuyama et al [2005] showed that groundwater flow within a permeable weathered granite bedrock contributed to streams year-round in one small headwater catchment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that CPT results are significantly affected by the presence of core stones. Moreover, Katsura et al (2009) demonstrated that the saturated hydraulic conductivity, K s , of the D L -class bedrock (10 − 4 cm s − 1 ) was dramatically lower than that of the soil (10 − 1 cm s − 1 ). These findings were based on core samples obtained from boreholes drilled on line C (Fig.…”
Section: Definition Of the Soil-bedrock Interface Using The Cone Penementioning
confidence: 99%
“…1c), were 12, 20, and 15 m, respectively; all were drilled by Katsura et al (2009) for geotechnical investigations and groundwater-level observations.…”
Section: Site C: Kiryu Experimental Watershedmentioning
confidence: 99%
See 2 more Smart Citations